Strengthening Local Policy Capacity for Sustainable Agroindustry MSMEs: A Governance Framework for Value-Chain Upgrading in Tanah Laut Regency, Indonesia - Annisa Zahrah (SWATANTRA, 2025)
Agroindustry micro, small, and medium enterprises (MSMEs) occupy a strategic position in rural economic transformation because they connect agricultural production with processing, market access, employment creation, and local value addition. However, in many Indonesian regions, agroindustry MSMEs continue to face persistent constraints related to fragmented institutional support, limited digital readiness, weak quality assurance, insufficient access to finance, and uneven integration into competitive value chains. This article examines how local policy capacity can be strengthened to support sustainable agroindustry MSME development in Tanah Laut Regency, South Kalimantan. Using a qualitative document-based policy analysis, the study synthesises secondary sources, policy literature, and regional development perspectives to construct a governance framework for agroindustry value-chain upgrading. The findings suggest that sustainable agroindustry development cannot be achieved through production assistance alone. It requires an integrated governance approach that combines institutional coordination, capability-building, digital market integration, green production practices, quality standardisation, and inclusive financing. The article proposes a six-dimensional policy framework consisting of regulatory alignment, institutional orchestration, entrepreneurial capability, digital infrastructure, sustainability upgrading, and participatory monitoring. The framework is intended to assist local governments, higher education institutions, business associations, and community actors in designing more coherent interventions for agroindustry MSMEs. The article contributes to public administration studies by showing that agroindustry development is not merely an economic or technical matter, but also a governance challenge involving policy coherence, administrative capacity, and collaborative public value creation.